Legal Review of The Use of Technology for International Trade Supervision - Adhi Susano; Muhammad Zainuddin; Irfan Rizky Hutomo (CV. Green Publisher Indonesia, 2026)
International trade continues to grow rapidly in line with increasingly complex technological advances. Monitoring cross-border trade activities presents a unique challenge for each country, particularly in ensuring compliance with applicable regulations and preventing legal violations, such as smuggling and illegal trade practices. In this context, the use of technology in international trade monitoring has become an urgent necessity. Various modern technologies, such as Artificial Intelligence (AI), blockchain, the Internet of Things (IoT), and big data analytics, have been implemented to increase the effectiveness and efficiency of trade monitoring. However, the use of these technologies raises various legal issues that require further study, including data protection, cybersecurity, legal compliance, and regulatory harmonization across jurisdictions. This study aims to analyze the legal framework governing the use of technology in international trade monitoring, identify emerging legal challenges, and provide recommendations for strengthening regulations in this area. The method used in this research is the normative juridical method, which focuses on the analysis of relevant laws and regulations at both national and international levels. The approaches used include statutory and conceptual approaches by examining various legal instruments related to technology-based trade oversight. The results of this research are expected to contribute to the development of regulations that are more adaptive and responsive to technological developments in international trade oversight. Furthermore, this research can also serve as a foundation for increasing synergy among countries in technology-based trade oversight to create a more transparent, secure, and equitable trading system.